2015
DOI: 10.1016/j.apgeog.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and community preparation for urban flooding in China

Abstract: Social capital can enhance community resilience to environmental change. Productive and trusted relations among social actors and effectual social norms can help local residents share resources, information and risks. The main objective of our study is to understand the ways in which social attributes and risk considerations influence adoption of resilient economic measures by individuals for reducing potential losses due to catastrophic rainstorm and flooding. This article provides evidence from China on how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…Lo and Chan (2017) find that active social networks increased peoples' intentions to prepare for extreme weather events. Lo et al (2015) also reveal a positive relationship between social capital and community resilience in China.…”
Section: Social Capital and Potential Links With Protection Motivatiomentioning
confidence: 78%
“…Lo and Chan (2017) find that active social networks increased peoples' intentions to prepare for extreme weather events. Lo et al (2015) also reveal a positive relationship between social capital and community resilience in China.…”
Section: Social Capital and Potential Links With Protection Motivatiomentioning
confidence: 78%
“…The above studies and many others suggest that there is no single uniform trend in extreme rainfall in urban areas. China's cities have been experiencing a rapid increase in urban flooding in recent decades (Lo et al, 2015;Zheng et al, 2016). A survey by the Ministry of Housing and Urban-rural Development (MOHURD) showed that 62% of the cities in China experienced urban flooding during 2008-2010 and that flood-induced losses in urban areas surpassed those in rural areas , which was thought to be related to extreme rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered likely that proliferation of a more generally negative attitude among study participants captures the recent general decline in public trust in political institutions , the experience of austerity associated with recent global financial events (Kinsella, 2012), and ongoing controversy concerning water policy reforms and efforts to introduce water charges in Ireland, (Kelly-Quinn et al 2014). These declines in public trust necessitate actions by local and national authorities given the relationship between trust and societal adoption of precaution-ary behaviours (Lo et al, 2015). For example, actions for improving public perception towards authorities within the realm of hydrological risk may include free system registration and assessment, free system remediation upon inspection failure, or free connection to a municipal treatment system if preferred.…”
Section: Discussionmentioning
confidence: 99%